Asparaginase‐associated pancreatitis in children with acute lymphoblastic leukaemia in the NOPHO ALL2008 protocol. (15th January 2014) - Raja, Raheel A.; Schmiegelow, Kjeld; Albertsen, Birgitte K.; Prunsild, Kaie; Zeller, Bernward; Vaitkeviciene, Goda; Abrahamsson, Jonas; Heyman, Mats; Taskinen, Mervi; Harila‐Saari, Arja; Kanerva, Jukka; Frandsen, Thomas L.; et al.
Summary L‐asparaginase is an important drug in the treatment of childhood acute lymphoblastic leukaemia (ALL). Treatment is associated with several toxicities, including acute pancreatitis. Clinical course, presentation, re‐exposure to L‐asparginase after pancreatitis and risk of recurrent pancreatitis within an asparaginase‐intensive protocol has been poorly reported. Children (1–17 years) on the ongoing Nordic Society of Paediatric Haematology and Oncology (NOPHO) ALL2008 protocol with asparaginase‐associated pancreatitis (AAP) diagnosed between 2008 and 2012 were identified through the online NOPHO ALL toxicity registry. NOPHO ALL2008 includes eight or 15 doses of intramuscular pegylated L‐asparginase (PEG‐asparaginase) 1000 iu/m2/dose at 2–6 weeks intervals, with a total of 30 weeks of exposure to PEG‐asparaginase (clinicaltrials.gov no: NCT00819351). Of 786 children, 45 were diagnosed with AAP with a cumulative risk of AAP of 5·9%. AAP occurred after a median of five doses (range 1–13), and 11 d (median) from the latest administration of PEG‐Asparaginase. Thirteen patients developed pseudocysts (30%) and 11 patients developed necrosis (25%). One patient died from pancreatitis. Twelve AAP patients were re‐exposed to L‐asparginase, two of whom developed mild AAP once more, after four and six doses respectively. In conclusion, re‐exposure to PEG‐asparaginase in ALL patients with mild AAP seems safe.